Creating the conscious law firm: What traditional law firms can learn from the conscious capitalism movement (Part 1) - Duperouzel, Christian (Law Council of Australia, 2020)
In the first part of a three-part series, Dr Christian Duperouzel examines the notion of conscious capitalism and explains why law firms need to integrate principles of conscious capitalism into their workings if they are to succeed in the new economy.